X-Ray Powder Diffraction Pattern of Fe(II) Complex of 1,3,5-Hexachlorotriphosphazene - JADON, S.P.S. (Asian Journal of Chemistry, 2010)
The complex of 1,3,5-hexachlorotriphosphazene (HCTP), (PNCI2)3 with iron(II) acetate has been synthesised and investigated spectrometrically. The frequencies for P—N→M, P—Cl2, P—N ring along with CH3COO- ion have been observed in its IR and laser Raman spectra. The electronic spectrum of the complex has shown bands according to charge transfer, 4T1g ← 4A1g and Pπ-Pπ transitions inferring the hexadentated coordination of two (PNCI2)3 rings to Fe(II)-acetate. X-ray diffractometric studies explain the coordination of two (PNCI2)3 deformed rings through Fe2+ ion bridging having sandwich structure in a triclinic geometrical packing.